EXTH-05. NON-CYTOTOXIC RADIATION ENHANCES DELIVERY OF ANTISENSE OLIGONUCLEOTIDES AND IMPROVES CHEMO-RADIATION EFFICACY IN BRAIN TUMOR XENOGRAFTS. (9th November 2020) - Wu, Jeffrey; Holland, Samantha; Muldoon, Leslie; Neuwelt, Edward; Ambady, Prakash
Abstract: Overexpression of O 6 -methylguanine DNA methyltransferase (MGMT) contributes to brain tumor chemo-resistance. Previously we found that non-cytotoxic radiation improved anti-MGMT Morpholino Oligonucleotides (AMONs) delivery to reduce MGMT levels in subcutaneous tumor xenografts. Here we evaluated if radiation enhanced the delivery of intravenous (IV) AMONs to rat brain and improved chemo-radiation therapy (CRT) efficacy using rat models of human brain tumors. Athymic nude rats bearing orthotopic cerebellar D283 medulloblastoma or intracerebral H460 non-small cell lung carcinoma (NSCLC) brain metastasis xenografts were used. The impact of cranial radiation on delivery of IV 3'-carboxyfluorescein labeled oligonucleotides across the neurovascular unit was evaluated using confocal microscopy. We found that high brain parencymal fluorescence in radiated compared to non-radiated rats. MGMT protein silencing was assessed by immunoblot in tumor-bearing rats 3 d after 2 Gy cranial radiation alone or followed in 1 d by IV AMONs (10.5 mg/kg). Radiation followed by AMONs reduced MGMT expression by 50% in both xenograft models. To evaluate efficacy, tumor-bearing rats received one dose of 2 Gy radiation plus oral temozolomide (20 mg/kg x 4d) with or without IV AMONs. AMONs concurrent with CRT reduced tumor volumes in the medulloblastoma model (p=0.012), and a similar trend was found in the NSCLC brain metastasis model. In conclusion, we demonstrate the use of a single clinically relevant radiation dose fraction to guide and enhance the delivery of oligonucleotides into brain tumor xenograft models to reduce MGMT levels and improve CRT efficacy.